2013
DOI: 10.1249/mss.0b013e31828ff9c6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Attenuates M1 Macrophages and CD8+ T Cells in the Adipose Tissue of Obese Mice

Abstract: The results suggest that exercise training reduces adipose tissue inflammation by suppressing infiltration of inflammatory macrophages and CD8 T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 32 publications
4
92
1
4
Order By: Relevance
“…Existing evidence in animals and humans indicates that exercise results in reduced expression of inflammatory genes and markers of immune cell infiltration in white AT (9,18,28,30,60,61). We found that voluntary WR-induced decreases in adiposity produced, by and large, similar downregulation of inflammatory genes in white AT (retroperitoneal) to that produced by decreases in adiposity with 30% DR regimen.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Existing evidence in animals and humans indicates that exercise results in reduced expression of inflammatory genes and markers of immune cell infiltration in white AT (9,18,28,30,60,61). We found that voluntary WR-induced decreases in adiposity produced, by and large, similar downregulation of inflammatory genes in white AT (retroperitoneal) to that produced by decreases in adiposity with 30% DR regimen.…”
Section: Discussionsupporting
confidence: 51%
“…Overall, our data indicate that the greatest effects of WR and DR on AT gene expression were in visceral AT. While visceral AT is highly susceptible to obesity-mediated inflammation/infiltration of immune cells (18,28,30,60,61), these data suggest that the phenotype of visceral AT is also highly amenable to reductions in adiposity. Given this close link between visceral AT expansion and inflammation in obesity (18,28,30,60,61), it is not surprising that measures of central adiposity in humans relate with metabolic and cardiovascular outcomes (21) and that interventions that result in weight loss are associated with improvements in insulin sensitivity and cardiovascular health (22).…”
Section: Discussionmentioning
confidence: 87%
“…However, studies in less overweight individuals have shown similar results [66]. Exercise also significantly reduced circulating levels of LPS and TLR4 activation, lowered M1 macrophage infiltration, and improved insulin sensitivity in mice fed a high-fat diet [67,68]. The temporal response to caloric restriction in diet-induced obese mice was recently examined [32].…”
Section: Diet and Lifestyle Interventionsmentioning
confidence: 95%
“…We also analyzed the characteristics of the macrophages in epididymal visceral AT by flow cytometry and found that exercise training not only decreased the cell number of macrophages, but also changed the ratio of the macrophage subsets in the AT of obese mice (Kawanishi et al. 2013). These results indicate that chronic endurance exercise may improve AT inflammation by changing the number and subset composition of macrophages.…”
Section: Introductionmentioning
confidence: 99%